Chinese cryptography: The Chinese Nationalist Party and intelligence management, 1927–1949. Issue 6 (2nd November 2018) - Kuzuoglu, Ulug
ABSTRACT: This paper is the first scholarly attempt to examine the history of Chinese cryptography and the role it played in building the intelligence network of the Chinese Nationalist Party (KMT) from 1927 to 1949. Rather than investigating the institutional structure of intelligence, I focus on Chinese characters, the primary medium that made cryptology and intelligence possible. Given that the Chinese writing system is by nature nonalphabetic and thus noncipherable, how did cryptography work in Chinese? How did the state and its scientists reengineer Chinese characters for the purposes of secret communication? This paper argues that due to the Chinese writing system itself, Chinese cryptography was bound to the use of codebooks rather than ciphers; thus, "codebook management" was central to building intelligence networks in China.